Electro-thermal modelling for plasmonic structures in the TLM Method - Elkalsh, Ahmed; Vukovic, Ana; Sewell, Phillip; Benson, Trevor M. (Springer, 2016)
This paper presents a coupled electromagnetic-thermal model for modelling temperature evolution in nano-size plasmonic heat sources. Both electromagnetic and thermal models are based on the Transmission Line Modelling (TLM) method and are coupled through a nonlinear and dispersive plasma material model. The stability and accuracy of the coupled EM-thermal model is analysed in the context of a nano-tip plasmonic heat source example.